Structural fatigue crack localisation based on spatially distributed entropy and wavelet transform. (1st September 2022) - Cui, Shihao; Maghoul, Pooneh; Liang, Xihui; Wu, Nan; Wang, Quan
Highlights: Spatial wavelet entropy is developed for crack localization on vibrating structures; Breathing crack is located by sudden change in spatial entropy on two crack sides; Effectiveness of the method is validated through numerical and experimental studies. Abstract: Fatigue cracks are inevitable in the service life of engineering structures and can cause unexpected severe structural failures if left unattended. During structural vibrations, fatigue cracks, specifically at the initial stage, exhibit a repetitive open-close breathing-like phenomenon. Breathing cracks cause irregularities, bi-linearity, or perturbations in the vibration responses at different locations in engineering structures. Entropy can be used to quantify the different irregularities or bi-linearity induced by breathing phenomenon. This paper presents a new breathing crack localisation method based on a spatially distributed wavelet entropy approach. A numerical analysis was conducted to validate the proposed method and illustrate the fundamentals of the proposed methodology by analysing the localisation of breathing cracks at different locations in a beam structure. Furthermore, the vibration responses of the beam with predefined breathing cracks were analysed using spatial wavelet entropy in a laboratory setup to further prove the feasibility of the proposed method. It was concluded that the proposed spatial wavelet entropy approach can be effectively used for breathing crack localisation in engineering structures.